COMPLICATIONS Nd:YAG LASER POSTERIOR CAPSULOTOMY AFTER PHACOEMULSIFICATION: A COMPARISON BETWEEN CRUCIATE AND CIRCULAR TECHNIQUES (Vietnam Journal of Community Medicine, 2026)
Objective: To determine and compare the incidence rates of complications and adverse events following Nd:YAG laser posterior capsulotomy using cruciate and circular techniques after phacoemulsification.Subjects and Methods: This randomized interventional comparative study conducted at Tra Vinh General Hospital from June to August 2022. Patients diagnosed with posterior capsule opacification (PCO) at least six months after phacoemulsification were randomly assigned to undergo Nd:YAG laser posterior capsulotomy using either the cruciate or circular technique.Results: The total energy used in the cruciate laser group was lower than in the circular laser group (69.43 ± 13.55mJ versus 123.56 ± 27.11mJ). No intraoperative complications were recorded in either the cruciate or circular Nd:YAG laser groups. Early postoperative complications included conjunctival hyperemia, corneal edema, and intraocular pressure elevation. There was no significant difference in the complication rates between the two techniques. All complications resolved completely within one month. No cases of cystoid macular edema, retinal detachment, uveitis, or macular hole were observed.Conclusion: Both cruciate and circular Nd:YAG laser posterior capsulotomy techniques are safe and effective after phacoemulsification. Although the circular technique requires higher total laser energy, postoperative complication rates are comparable between the two techniques.
Keywords: Posterior capsule opacification, Nd:YAG laser capsulotomy, complications, cruciate technique, circular technique.